The Effect of Using a Teaching Aid on Learning Backswing to Handstand on Rings in Youth Artistic Gymnastics - Mohameed Hamza; Thamer Turky; Jamal Hamza (College of Physical Education and Sport Sciences, 2022)
The research aimed at designing a teaching aid for learning backswing into handstand as well as identifying its effect on learning skill performance. The researchers hypothesized statistical differences between pre and post-tests in favor of the research group. They used the experimental method on six (13 - 16) year-old Baghdad club gymnasts. The researchers used the one group design in which all players perform pretests followed by special tests on the teaching aid than are tested posttests. The researchers conclude that the teaching aid positively affected learning the skill as well as the teaching aid was very good and endured the performance of all gymnasts. The researcher recommended making similar studies using the same teaching aid on other artistic gymnastics apparatuses and other motor skills.